Trends and current issues in common labor market of EAEC - A. A. Yerezhepova (Хабаршысы. Экономика сериясы, 2016)
The article analyzes the state of the labor market and the formation of the Eurasian space, the problem of formation of effective labor market and the role of the state in maintenance and development. In this regard, the relationship and identified problems in the formation of a common labor market in the framework of the EAEC, which guarantees the treaty establishing the EAEC. The article discusses the characteristic features of modern migration and possible socio-economic consequences of international labor migration, areas of improvement and control measures the total labor market, adopted by states that would extend social rights and labor guarantees for foreign workers from the EAEC countries. Such measures would stimulate the movement of the mobile workforce in a single economic space, which in turn promotes the formation of a common labor market and the provision of social protection measures workforce guaranteed contract states participating.